S.E.C Report on the Securities Markets: Discussion - Robbins, Sidney M.; Ames, Amyas; Sauvain, Harry C. (Journal of Finance, 1966)
Sidney M. Robbins, Amyas Ames, Harry C. Sauvain, S.E.C Report on the Securities Markets: Discussion, The Journal of Finance, Vol. 21, No. 2, Papers and Proceedings of the Twenty-Fourth Annual Meeting of the American Finance Association, New York, New York, December 28-30, 1965 (May, 1966), pp. 339-344